2020
DOI: 10.1002/lio2.340
|View full text |Cite
|
Sign up to set email alerts
|

Adenotonsillectomy and postoperative respiratory adverse events: A retrospective study

Abstract: Objectives Postoperative respiratory adverse events (PRAEs) are known complications following adenotonsillectomy (AT). Clinical data at a single institution were reviewed to investigate the factors that may contribute to PRAEs in the postanesthesia care unit (PACU). The relationship between PRAEs in the PACU and escalation of care, defined as either an unplanned admission for outpatient surgery or unplanned pediatric intensive care unit (PICU) admission, was investigated. Methods The perioperative records for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 19 publications
0
17
0
1
Order By: Relevance
“…2,4,[8][9][10][11][12][13][14][15][16][17][18][19][20] See Figure 1 for a PRISMA flow diagram illustrating the study selection process. 2,4,[8][9][10][11][12][13][14][15][16][17][18][19][20] All included studies were observational: 14 retrospective and one prospective. 12 One study had a control group for outcome comparison.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,4,[8][9][10][11][12][13][14][15][16][17][18][19][20] See Figure 1 for a PRISMA flow diagram illustrating the study selection process. 2,4,[8][9][10][11][12][13][14][15][16][17][18][19][20] All included studies were observational: 14 retrospective and one prospective. 12 One study had a control group for outcome comparison.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining six studies reported on post-operative complications within the first 24 h, although it was unclear what proportion of these patients underwent the procedure as a day case. 4,[10][11][12]16,18 Four studies stratified patients by comorbid and functional status using the American Society of Anaesthetists (ASA) scale, within these studies, the ASA ranged from 1 to 3. [15][16][17][18]…”
Section: Key Pointsmentioning
confidence: 99%
“…Respiratory complications can occur intra-operatively, in the PACU, or post-operatively. Major respiratory complications include bronchospasm, laryngospasm, post-obstructive pulmonary edema, airway obstruction, aspiration pneumonitis, pneumonia, or cardiopulmonary arrest [8,51]. These events typically result in reintubation, CPAP/BIPAP therapy, placement of a nasopharyngeal or oropharyngeal airway, bag mask ventilation, an unplanned admission of the patient to the hospital, elevation of care to the intensive care unit (ICU), pulmonary edema, or, rarely, death [52].…”
Section: Respiratory Complicationsmentioning
confidence: 99%
“…There are certain patient specific risk factors for hypoxemia within the first 24 h post-operatively that have been identified. These include patients with Trisomy 21, obesity, age, black race, coexistent cardiac disease, clinical diagnosis of OSA, coexistent neurologic disease, or a prior diagnosis of pulmonary disease [50,51,53]. Given the lack of standardization in the literature defining what exactly characterizes a hypoxic event, the reported incidence varies from 5% to 30%, with a meta-analysis reporting a 9.4% overall incidence [50].…”
Section: Respiratory Complicationsmentioning
confidence: 99%
“…[3][4][5] For these patients, the decision to undergo these otolaryngologic procedures and the use of perioperative opioids often mandates prolonged periods of observation or overnight hospital admission due to the potential risk of postoperative respiratory depression. 6,7 An opioid-sparing anesthetic technique includes adjunctive non-opioid agents using a multi-modal approach employing a combination of non-opioid medications which target various analgesic pathways. 8 These techniques are becoming more popular not only to decrease the incidence of adverse effects related to opioids, but in identifying clinical opportunities to minimize opioid use amidst the backdrop of the national opioid crisis which affects both the adult and pediatric population.…”
Section: Introductionmentioning
confidence: 99%